2016
DOI: 10.1007/s00345-016-1911-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tumor histology and grade on treatment success of percutaneous renal cryoablation

Abstract: Association of higher grade and clear cell histology with recurrence and progression suggests need for increased emphasis on preoperative risk stratification by biopsy, with grade 1 and non-clear cell RCC being associated with improved treatment success than higher grade and clear cell RCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
3
4
0
Order By: Relevance
“…However, tumor size did not correlate with RFS rates, in agreement with other series [8,10]. Additionally, RFS rates were not significantly affected by tumor histotype, while Beksac et al [24] found an association between clear cell histology and progression. It is worth noting that treatment efficacy was not significantly affected by the type of anesthesia, including local anesthesia only.…”
Section: Discussionsupporting
confidence: 82%
“…However, tumor size did not correlate with RFS rates, in agreement with other series [8,10]. Additionally, RFS rates were not significantly affected by tumor histotype, while Beksac et al [24] found an association between clear cell histology and progression. It is worth noting that treatment efficacy was not significantly affected by the type of anesthesia, including local anesthesia only.…”
Section: Discussionsupporting
confidence: 82%
“…This study showed a local recurrence rate of 2.9% at one year, of 2.9% at three years, and of 1.8% at five years, appearing consistent with some studies establishing a local recurrence rate between 0% and 5% in the first three years of follow-up [7,10,12,17,29] and significantly lower compared to others that report recurrence rates ranging from 7% to 16% [6,9,16,42,44,45] at three years. Similarly, long-term results are strongly encouraging, showing a local recurrence at five years of 1.8% against the 3% evident in some studies [8,46] and even 13% in other series [16,42,43].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, this incidence rate disproportionally rose to 72% between 2006 and 2007 [4]. The incidence rate of RCC is still growing, with an increase of about 2.4% per year, on account of a rising number of abdominal imaging exams performed for non-renal symptoms, determining an incidental diagnosis in more than 50%-60% of cases of renal cancer [1,3,[5][6][7][8][9][10]. In particular, recent years showed a considerable increase in incidental detection of the small lesions intended as masses less than 4 cm in size, typically asymptomatic and generally affecting elderly [4].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging data suggest that for both cryoablation and RFA, patients with non-clear cell and lower grade histologies may have improved outcomes. 137 Patient counseling about thermal ablation should include a discussion of the risks of local recurrence, and potential need for re-intervention. Newer energy-ablative modalities have the potential to become additional nephron-sparing options, but further investigation is needed.…”
Section: Tumor Ablation Techniquesmentioning
confidence: 99%